Detailed soil survey as support for the planning of land use - Grahl dos Santos, Pablo; Antonio de Almeida, Jaime; Sequinato, Letícia; Benedito Schimalski, Marcos (Revista de Ciências Agroveterinárias, 2015)
Appropriate soil use is required so that the agricultural holding is conducted using conservationist bases, through the rational planning applied to each glebe of land, taking into consideration all of its main attributes. The objective of this study was to execute a detailed soil survey, providing support for planning the sustainable use of natural resources based on their agricultural potential. The study was carried out in Lages, SC, Brazil, at latitude 27°44'54.11'' south and longitude 50°05'08.09'' west, with an average altitude of 884 m and a humid mesothermal climate. The survey was supported by global positioning system, photogrammetry, photo interpretation, and geographic information system. It was proceeded a general and morphological description of soil profiles and a horizons sampling collection for analysis. Based on the soil’s physical and chemical properties, the soils were taxonomically classified in phase levels, according to the Brazilian System of Soil Classification. The mapping unit’s limits were identified through their relationships with soil and topography surfaces by means of observation and sampling along the top sequences, outlined using relief phase. The legend for the final survey was prepared as well as a pedological map containing the agricultural suitability classes used for planning.